2021
DOI: 10.3926/jiem.3331
|View full text |Cite
|
Sign up to set email alerts
|

Demand Driven Material Requirements Planning (DDMRP): A systematic review and classification

Abstract: Purpose: Demand Driven Material Requirements Planning (DDMRP) aims to deal with variability by adjusting inventory levels while maintaining, or even increasing, customer service levels. This approach bridges the push and pull approaches. Even though it first made its appearance in 2011, research in this field remains relatively limited. This paper aims to measure the spatiotemporal evolution of the DDMRP, its scope and context of implementation, and the research lines studied in that field in order to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Both Erraoui et al (2019) and Ptak and Smith (2019) underline the importance of the inventory positioning step in a demand-driven distribution network. However, they didn't propose a tool to make positioning decisions (Azzamouri, Baptiste, Dessevre & Pellerin, 2021), in contrast to this paper. The principal contributions of this paper are i) to propose a mathematical model to optimize buffer positioning in a demand-driven distribution network, and ii) to evaluate the performance of the DDDRP approach compared to the conventional DRP approach.…”
Section: Ddmrp and Dddrp Conceptsmentioning
confidence: 89%
“…Both Erraoui et al (2019) and Ptak and Smith (2019) underline the importance of the inventory positioning step in a demand-driven distribution network. However, they didn't propose a tool to make positioning decisions (Azzamouri, Baptiste, Dessevre & Pellerin, 2021), in contrast to this paper. The principal contributions of this paper are i) to propose a mathematical model to optimize buffer positioning in a demand-driven distribution network, and ii) to evaluate the performance of the DDDRP approach compared to the conventional DRP approach.…”
Section: Ddmrp and Dddrp Conceptsmentioning
confidence: 89%
“…As recently emphasized by Azzamouri, Baptiste, Dessevre, and Pellerin (2021), the founders of the DDMRP gave only a few details on parameter definition. In Ptak and Smith (2016), they set the parameters as follows:…”
Section: Sizing the Ddmrp Buffersmentioning
confidence: 99%
“…Through their study of the literature, Azzamouri et al (2021) showed a tendency to use different types of simulations in order to obtain new scientific results on the DDMRP. The most prominent one is Discrete Event Simulation (DES), that allows to model complex workshops and specific DDMRP behaviors.…”
Section: Sizing the Ddmrp Buffersmentioning
confidence: 99%
“…They conclude that the main criticality of the method is the high subjectivity affecting the positioning of the buffers. On the other hand, Azzamouri et al (2021), carry out a systematic literature review about research dealing with the DDMRP published between 2011 and 2020 in different languages. They analyze the extensions of the method in the literature, and present a taxonomy.…”
Section: Literature Reviewmentioning
confidence: 99%